Physical, phase transformation and elastic properties of wollastonite glass-ceramics fabricated using eggshell and waste glass - Mohamad Yamin, Nurul Afiqah (2022)
Wollastonite, also widely recognized as calcium silicate (CaSiO3), has received extensive research due to its numerous application such a tiles and cement. A lot of attention has been paid recently to the physical characterization, transformation of phases, and elastic wollastonite glass-ceramics properties. The main aims of this research are to fabricate wollastonite glass-ceramics from waste products and to study the physical, structural, and elastic properties of wollastonite glass-ceramics. A series of glass with combine composition derived from ES–ZnO–B2O3–SLS and classified as EZBSLS glasses were prepared via melt-quenching method with empirical formula, x(ES)–5ZnO– 10B2O3–100-x(SLS) where x = 15, 20, 25, and 30 wt.%. The wollastonite glass-ceramics were originated from the parent glasses by a controlled heattreatment process at various temperatures of 700, 800, 900 and 1000 °C at 2 hours holding time. The detail of chemical composition of ES and SLS glass was discovered by using energy dispersive X-ray fluorescence (EDXRF). The results indicated that the major elements in SLS glass was SiO2 with 70.5 wt.%. Meanwhile, for ES, the main element composed of CaO with 96.8 wt.% which confirms that the SLS glass waste and ES can be used as SiO2 and CaO source. Archimedes method was used to measure bulk density of EZBSLS glasses and wollastonite glass-ceramics. Meanwhile, the molar volume of the samples were calculated by using formula from the molecular weight of the atom divided by the density of the sample. Based on the result, the bulk density of the EZBSLS glasses was increased from 2.684 to 2.779 g/cm3 with the increasing of ES content. Furthermore, the density of the wollastonite glassceramics was also increased along with the advancement of heat-treatment temperature and the highest density referred to ELZBSLS4 at 1000 °C which is 2.843 g/cm3. The structural properties of EZBSLS glass and wollastonite glassceramics samples were determined by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Fourier Transform Infrared (FTIR) Spectroscopy. The XRD result revealed no peak appeared proving that the EZBSLS glasses are fully amorphous in structure. For wollastonite glassceramics, the analysis showed the wollastonite crystal phase started to grow at the heat-treatment temperature of 800 °C and the peak intensity linearly increased with the increment of ES content and heat-treatment temperatures. From the result, the intense peak of wollastonite crystal phase (JCPDS 84-654) was detected at 900 °C with the optimum 25 wt.% ES content. FTIR reflection spectroscopy was the used to assess structural of glass and wollastonite glassceramics in the range 400 – 4000 cm-1. The presence of several types of vibration such as Ca–O, Si–O–Si, and the detection of Ca-O-Si bands in FTIR measurement methods confirms the formation of wollastonite crystal phase in the EZBSLS glass matrix. Furthermore, the microstructure of wollastonite glass-ceramics was analyzed at 900 °C and the 25 wt.% ES sample showed an early stage of homogenous distribution in uniform shape of wollastonite crystal. Next, the EZBSLS glasses and wollastonite glass-ceramics were analyzed by their elastic properties by non-destructive ultrasonic velocity testing. As can be concluded that EZBSLS3 heat-treated at 900 °C is the most stable and optimal with value of bulk and Young’s modulus are 167.538 and 143.572 GPa.